The stability of an irrigation canal system - Bounit, Hamid (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we examine the stability of an irrigation canal system. The system considered is a single reach of an irrigation canal which is derived from Saint-Venant's equations. It is modelled as a system of nonlinear partial differential equations which is then linearized.
Keywords: Saint-Venant equation; dimensionless; symmetric hyperbolic equation; internal stability; transfer function; input-output stability; regular systems